Evaluation of antidiabetic and antioxidant properties and metabolite profiling of Momordica charantia fruit using metabolomics approach - Vikneswari Perumal (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
Momordica charantia Linn (Cucurbitaceae) has been widely commercialized based on traditional usage as an antidiabetic product. However, the scientific evidence of its antidiabetic activity is not sufficient. Hence, the major aims of this research were to evaluate the antidiabetic activity of M. charantia fruit through proton-nuclear magnetic resonance (1H-NMR) spectroscopy based metabolomics, to investigate its mechanism of action, to profile the identified antioxidants as antidiabetic agents through liquid chromatography-mass spectrometry (LC-MS) and gas chromatography-mass spectrometry (GC-MS) based metabolomics, and to develop a validated regression model using fourier transform infra-red spectroscopy (FT-IR) based fingerprinting. Initially, the fruit was extracted by the solvent with different ethanol in water concentration (0, 20, 40, 60, 80, 100%, v/v). Then, the extracts were subjected to different in vitro assays. The 80% aqueous ethanolic extract possessing the highest in vitro bio-activity was chosen for further in vivo antidiabetic evaluation utilizing 1H NMR based metabolomics approach. In vitro dipeptidyl peptidase-4 (DPP-IV) inhibitory and 3T3-L1-cell glucose uptake activities were also tested for the same extract to explain its mode of action in relation to the metabolomics results. LC-MS and GC-MS based metabolomics approaches were applied to profile the bioactive compounds present in the extract. Finally, a validated calibration model was developed using FT-IR based fingerprinting. The 80% ethanolic extract showed a high inhibitory activity on 1, 1-diphenyl-2 picrylhydrazyl (DPPH) radical and high ferric reducing antioxidant power, but failed to exhibit inhibitory activity against α-glucosidase and xanthine oxidase enzymes. Thereby, the antidiabetic activity of this extract was further evaluated using streptozotocin obese-diabetic induced rats (STZ ob-db). The results showed that the administration of the 80% ethanolic extract at 300 mg/kg bw for 4 weeks significantly (P < 0.05) reduced the blood glucose level and normalized the blood lipid profile of rats. However, the data obtained from the metabolomics showed that the metabolite profiles of the serum and urine of rats could not be fully normalized by the 80% ethanolic extract and metformin. The identified biomarkers in serum and urine were 2-hydroxybutyrate, leucine, adipate, alanine, acetate, succinate, 2-oxoglutarate, dimethylamine, creatine, creatinine, betaine, glucose, taurine, phenylacetylglycine, allantoin and hippurate. Furthermore, it was found to ameliorate the energy metabolism through the improvement of 3T3-L1-cell glucose uptake and inhibition DPP-IV but not through the inhibition of α-glucosidase and xanthine oxidase. This extract displayed strong antioxidant activities which further showed a positive correlation to antidiabetic activity. LC-MS and GC-MS based metabolomics approaches helped to identify several antioxidants in this extract such as ascorbic acid, margarolic acid, brevifolincarboxylic acid, quercetin 3-O-glycoside, kuguacin H, cucurbitacin E, 3-malonylmomordicin I, goyaglycoside G, gentiobiose, glucose, galactonic acid, palmitic acid, galactose, mannose, and fructose. Finally, the validated regression model based on the FT-IR based fingerprinting has been successfully developed for the first time through this study in regard to predict the antioxidant activities of the new set of the extracts of M. charantia. In conclusion, this study showed that the M. charantia fruit extract has a great potential to be efficaciously used in the management of diabetes.